Development of sorting methods based on physical and aerodynamic properties of off-ground harvested almonds - Chen, Chang; Khir, Ragab; Zhang, Rentang; Cao, Xiangyu; Ning, Zhaokun; Shen, Yi; Wang, Tianxin; Pan, Zhongli (International Journal of Agricultural and Biological Engineering, 2021)
This research was conducted to develop an effective approach to sort off-ground harvested almonds for efficient drying based on their physical and aerodynamic properties. Three popular varieties were studied, including Nonpareil, Monterey, and Fritz. The insect damage, axial dimensions, weight ratio, moisture content, bulk density and terminal velocity of in-hull almonds, in-shell almonds and loose hull at harvest were measured. The results indicated that the insect infestation percentage in the off-ground harvested almonds ranged from 2.5% to 6.3%, which was about half of those in the conventional on-ground dried almonds. Loose hulls and in-hull almonds had higher moisture content and wider moisture distribution than those of in-shell almonds, suggesting that sorting of the almonds and drying them separately are necessary for efficient handling and processing. Thickness was the smallest axial dimension of an almond, and thus could be used for sorting. The cut-off sizes of 16.5 mm, 21.3 mm and 21.1 mm could separate 100% of the in-shell almonds from the rest for Nonpareil, Monterey and Fritz varieties, respectively, as the first step. In the second step, applying terminal velocities of 12.3 m/s, 11.8 m/s and 12.2 m/s could efficiently separate the in-hull almonds and loose hulls for Nonpareil, Monterey and Fritz varieties, respectively. Overall, up to 76.7% of the loose hulls could be removed, and up to 3.3% in-hull almonds may be lost during the sorting process. The experimental results provided important information for developing efficient sorting and drying methods with improved throughput, energy efficiency, better quality and safety of off-ground harvested almonds.Keywords: almond, off-ground harvesting, physical properties, aerodynamic properties, sorting, dryingDOI: 10.25165/j.ijabe.20211402.6090Citation: Chen C, Khir R, Zhang R T, Cao X Y, Ning Z K, ShenY, et al. Development of sorting methods based on physical and aerodynamic properties of off-ground harvested almonds. Int J Agric & Biol Eng, 2021; 14(2): 218–225.